Design of vertically stiffened steel plate walls under combined uniaxial compression and shear loads. (August 2020) - Xu, Zhaoyu; Tong, Genshu; Zhang, Lei
Abstract: Elastic buckling of stiffened steel plate walls (S-SPWs) under combined compression and shear was studied focusing on the stiffness demand on stiffeners to implement subpanel's buckling mode. Flat-bars and closed form stiffeners were considered. Threshold stiffness of stiffeners is presented for elastic buckling of subpanels of S-SPWs in pure compression, pure shear and combined compression and shear. The effect of stiffeners' torsional stiffness has been included. Then the elastic–plastic (E-P) buckling of S-SPWs under combined compression and shear was studied. A criteria was established to identify the E-P shear buckling stress under a prescribed compression stress for S-SPWs with given stiffness of stiffeners. Threshold stiffness of stiffeners was taken on the buckling stress – stiffness curve at the transition point as the E-P buckling shear stress reaches a plateau. The demand of keeping stiffeners straight when stiffeners are compressed simultaneously has been incorporated in such defined threshold stiffness. Equations for threshold stiffness of flat-bars and closed form stiffeners are proposed separately and comparisons with finite element results show good accuracy.